Odpowiedzi

2010-02-20T11:09:14+01:00
X²-6x+8 dla:

a)x=4;
x²-6x+8 = 4²-6 * 4+8 = 16 - 24 +8 = 0

b)x=2;
x²-6x+8 = 2²-6*2+8 = 4-12+8 = 0

c)x=1;
x²-6x+8 = 1²-6*1+8 = 1-6+8 = 3

d)x=1/5;
x²-6x+8 = ⅕²-6* ⅕ +8 = ¹/₂₅ - ⁶/₅ +8 = ¹/₂₅ - ³⁰/₂₅ +8 = -²⁹/₂₅ + 8 = -1⁴/₂₅ + 7²⁵/₂₅ = 6²¹/₂₅

e)x=0,2;
x²-6x+8= (0,2)²-6* 0,2+8 = 0,04 -1,2 +8 = 6,84
2010-02-20T11:14:18+01:00
X²-6x+8
wszystko podstawiany za x....

a)4²-6*4+8= 16-24+8=0
b)2²-6*2+8=4-12+8=0
c)1²-6*1+8=1-6+8=3
d)⅕²-6*⅕+8=1/25-6/5+8=1/25-30/25+8=-29/25+8=6 i 21/25
e)(0.2)²-6*0.2+8=0,04-1,2+8=6,84